Exact Solution of Mesh Stiffness and Analysis of Tooth Profile Parameters for Asymmetric Gear Pairs - Yang Yong; Hu Junhua; Shi Zhiqi; Zhou Qinghua; Wu Jian (Jixie chuandong)
Asymmetric gears are a new type of involute gears with different pressure angles on each side of a gear tooth. Gear tooth profile parameters have a great influence on the performance of a gear pair, such as its tooth profile shape, motion characteristics, bearing capacity, transmission efficiency, dynamic characteristics and so on. Asymmetric tooth geometry formulas based upon a rack-type tool are derived following Litvin's vector approach. Then a precise calculation model for meshing stiffness of asymmetric gear is proposed and validated to be effective by comparing with a finite element model separately. Further, the influence of cutting tool tip fillet radius, gear pressure angle and contact ratio on gear meshing stiffness is quantified parametrically. The research results indicate that gear meshing stiffness can be improved effectively with the increase of pressure angle and cutting tool fillet radius. The influence of the pressure angle is relatively greater. With the increase of the pressure angle, not only will the thickness of tooth root increase, which is beneficial to improve the bearing capacity of the gear, but also the thickness of tooth tip and contact ratio will decrease, which is prone to evoke tooth tip fractures. In asymmetric tooth profile design, it is suggesting that the involute pressure angles are set according to actual working conditions.